An exploration of the personality characteristics and adverse childhood experiences (ACEs) of non-offending mothers - Dawson, Hannah (2021)
The non-offending partner (NOP) in cases of intrafamilial child sexual abuse has received limited empirical attention in comparison to the considerable body of literature examining victims and perpetrators of child sexual abuse and even less focus has been drawn to NOPs in cases of non-sexual familial abuse. There is growing evidence that demonstrates that non-offending mothers, more generally, experience significant loss and trauma following the discovery of their children’s sexual victimisation by a family member, particularly where the perpetrators are their partners. An understanding of the non-offending mother’s experience is crucial to guiding statutory agencies and therapeutic interventions when working with these families. Therefore, the aim of this study was to address the gap in the existing literature, by conducting exploratory investigations of the personalities and adverse childhood experiences of a specific group of non-offending mothers (NOM) of not just children who have been sexually abused by the mother’s partner, but who have experienced all kinds of abuse. It was hoped that findings might inform treatment targets and practices for the mother during recovery journeys of families, post-disclosure. The presented studies used retrospective data, gathered from assessments conducted for child care proceedings and comprised of two stages; in the first stage, the area of NOMs’ personality was revisited and updated from existing literature, seeking to address gaps identified from a systematic review. The second stage of the study utilised this personality information, but looked at it more functionally, pairing it with information regarding Adverse Childhood Experiences (ACEs). The findings of the studies confirmed the heterogeneity of the NOM population, where experiences differed across cases, but where there was a high volume of adversity in the childhoods of NOMs, nonetheless. Although similarities could be drawn with certain personality characteristics being more commonly present, such as social disinhibition, resentment, and anxiety, a significant ‘type’ of NOM was not identified. Further, it was recognised from the outset that the specificity of the NOM group within the overall NOP population narrowed the applicability of any findings. To conclude the research, a critique of methods used to assess NOM support following their child’s disclosure was conducted. The overall findings, limitations and implications were compiled and discussed.